Turkey and EU (the European Union): the integration problems - Buyenbayeva, Z. K. (Journal of Oriental Studies, 2016)
The article deals with the problem of integration of Turkey into the European Union and the Turkish implementation of EU’s conditions for joining into the Union. Consequently, the article is analyzed the legislative changes and replenishment in the Constitution of the Republic of Turkey for entering the EU. By today’s relationship between the EU and Turkey, there is a point that Turkey needs another additional 10-15 years of testing.